Apparent diffusion coefficient predicts MGMT status in adult-type diffuse gliomas and is correlated with Ki-67 proliferation index - Zhu, Feng-Ying; Zhuo, Li-Yong; Wang, Tian-Da; Wang, Jia-Ning (Frontiers in Oncology, 2025)
PurposeTo evaluate the predictive value of apparent diffusion coefficient (ADC) for O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation and its correlation with Ki-67 proliferation index in adult-type diffuse glioma, stratified by isocitrate dehydrogenase (IDH) subtype.MethodsThis retrospective study enrolled 94 patients with pathologically confirmed glioma (2017–2024). ADCmin, ADCmean, and relative ADC (rADC) values were derived from diffusion-weighted imaging (b=1000 s/mm²). MGMT methylation, IDH mutation, and Ki-67 index were assessed by Pyrosequencing and immunohistochemistry. Receiver operating curve analysis was performed to evaluate diagnostic performance, and Spearman correlation was used to link ADC with Ki-67 index.ResultsMGMT-methylated gliomas exhibited significantly higher ADCmin (0.86 vs. 0.74 × 10-³mm²/s, p = 0.013) and rADCmin (1.12 vs. 0.95, p<0.001). In the IDH-wild-type subgroup, rADCmin achieved an AUC of 0.78 (cutoff=1.10, sensitivity=80.0%). All ADC parameters were negatively correlated with Ki-67 (ρ=- 0.32 to -0.24, p<0.05).ConclusionADC values, particularly rADCmin, were identified as non-invasive biomarkers for MGMT methylation prediction in IDH-wild-type gliomas. An inverse correlation between ADC and Ki-67 index supported their utility for assessing tumor proliferation. Standardizing rADC would improve its clinical applicability across imaging platforms.